THE IMPLEMENTATION OF DISCOVERY LEARNING IN EFL CLASSROOM - Muhammad . Hardi; Rahmad . Husein; Meisuri . . (LINGUISTIK TERAPAN, 2022)
ABSTRACT The objective of this study was to describe the ways the discovery learning implemented in teaching and learning process. The data of this study were teachers’ implementation while they were implementing discovery learning. Participant observation technique was performed to collect the data. Based on the data analysis, it was found there were differences between the activities designed and implemented since the teacher did not understand nor comprehend the model completely. Furthermore, all of the observed teachers conducted the activity of data collection by explaining the material to the students and mostly focused on the grammar and not letting the students collecting the data by themselves. Moreover, during the implementation, the male teacher tended to draw a pattern of explaining and assigning while the female teachers tended to give stimulation first and followed with explaining and assigning. It showed that there was difference in the way of implementing discovery learning between the teachers based on their gender.